“Making Sense”: Aesthetic Counterpowers in Activist Media Practices - Brunner, Christoph (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
This article engages with the activities of the alternative international media centre FC/MC which was established and operated during the 2017 G20-summit in Hamburg. Rather than following established narratives on alternative media or mobilising discourses on aesthetics of resistance in the arts, the specific operational logics of affective and preemptive politics of perception define the main scope of developing what is termed “activist sense” and the emergence of potential “aesthetic counterpowers” as part and parcel of an affective politics of perception. Drawing on the conception of affect in social media studies and on the notions of field and information in the works of Gilbert Simondon, the FC/MC will be analysed as a building block in the overall infrastructure of affective resistance against dominant and platform-based narratives of violence and threat amplified by mainstream media. Through a field-based conception of affect and perception, the question of “making-sense” takes on a pervasive yet potentially more inclusive and activating dimension of future forms of media-infused modes of resistance.